Enhancing Student Emotion Regulation: A Cognitive Approach to NSSI - Maghfira, Mindy; Suhana, Suhana (Universitas Negeri Malang, 2025)
Non-Suicidal Self-Injury (NSSI) is a maladaptive coping mechanism frequently observed among university students as a response to unregulated emotional distress, without suicidal intent. This case study aims to describe the psychological dynamics and assess the effectiveness of a cognitive-based intervention in helping a student manage NSSI within the context of higher education. The participant was a 27-year-old female with a history of self-harming behavior since her undergraduate years. Data were collected through interviews, observations, and psychological assessments using the WBIS, Rorschach Inkblot Test, projective drawing tests, and the Edwards Personal Preference Schedule (EPPS). The assessment revealed unresolved emotional conflict, unmet social affiliation needs, and difficulties in emotional expression. Contributing factors included an authoritarian parenting style, limited emotional involvement from the father, and ongoing academic and social stressors. The intervention was delivered over six counseling sessions using a cognitive approach combined with emotional regulation education and assertiveness training. The results indicated a reduction in self-harm urges, improvement in emotional regulation skills, and the development of more adaptive coping strategies. These findings support the effectiveness of cognitive-based interventions in educational settings for addressing NSSI rooted in emotional conflict and poor emotional expression, highlighting the importance of integrating such strategies into mental health services on university campuses.